Composition analysis and tyrosinase inhibitory activity of Cinnamomum cassia Presl leaf hydrosol and Cymbopogon citratus (DC.) Stapf leaf hydrosol. Issue 11 (2nd September 2022) - Yu, Bingying; Wu, Kegang; Duan, Xuejuan; Zhang, Tong; He, Dong; Chai, Xianghua
Abstract: Hydrosol is a natural aromatic product possessing broad application prospects as a food preservative; however, limited information is available regarding its anti‐tyrosinase activity. Here, we investigated the inhibitory effects of Cinnamomum cassia Presl leaf hydrosol (CCPH) and Cymbopogon citratus (DC.) Stapf leaf hydrosol (CCSH) on tyrosinase activity. The primary components of CCPH and CCSH were cinnamaldehyde (82.1%) and citral (52.3%), respectively. The aromatic compound, terpenoid, and nitrogen oxide detectors within the electronic nose yielded higher response values for the two hydrosols. The IC50 values for CCPH, CCSH, cinnamaldehyde, and citral in regard to their effects on tyrosinase were 84.8 ± 15.5 (vol%), 23.9 ± 2.0 (vol%), 53.3 ± 10.7 mM, and 21.0 ± 6.5 mM, respectively. According to Lineweaver‐Burk plot analyses, cinnamaldehyde and citral are both non‐competitive inhibitors. Both CCPH and CCSH inhibited browning of mushrooms ( Agaricus bisporus ). These results suggest that hydrosols could be used as potential tyrosinase inhibitors in the food additive and cosmetic industries. Novelty impact statement: The primary components of CCPH and CCSH were cinnamaldehyde (82.1%) and citral (52.3%), respectively. The hydrosols and their primary components exerted an inhibitory effect on tyrosinase. CCPH and CCSH could inhibit the browning of mushrooms ( Agaricus bisporus ).